SmartScore 99
SmartScore 86
SmartScore 92
Here's the question you clicked on:
Spectrum
sin(a-b) = sinacosb+cosasinb for all values of a and b. True or false?
False.
evidence?
It should be sin(a - b) = sin(a)cos(b) - cos(a)sin(b)
Let's do it this way to evidence more: sin(a - b) = sin(a)cos(b) - sin(b)cos(a) sin(a + b) = sin(a)cos(b) + sin(b)cos(a) SO, cos(a - b) = cos(a)cos(b) + sin(a)sin(b) cos(a + b) = cos(a)cos(b) - sin(a)sin(b) Simple.
Thank you @Praja_01
Thank you very much @Spectrum.
Not the answer you are looking for?Search for more explanations.